The Literary Culture of Russian-Speaking Israel. Disputes Around The “Nationality” of Literature - Lenart , Agnieszka (Archiwum Emigracji. Studia – Szkice – Dokumenty, 2024)
Original issue: “Archiwum Emigracji” 2014, no. 1-2 (20-21) https://apcz.umk.pl/AE/article/view/AE.2014.006